Stasis in the population of Metaponto : analysis of environment, health, and political unrest - Viviani, Brittany Jean (My University, 2013)
The Greek colony of Metaponto offers an invaluable insight to the study of both rural and urban populations. Analysis of population is an important study to be able to examine social, political, and economic impacts of the time and how a group of people dealt with these stressors. Starting around 500 B.C. Metaponto experienced a period of great prosperity followed by a period of stasis starting around 425 B.C. Analysis was completed to understand whether stasis was the result of 1) epidemic disease, 2) environmental degradation, 3) political unrest, and 4) a combination of factors. Data used included archaeological data and historical accounts of Metaponto from Greek historians. Stress and possible warfare from different groups of people in the Mediterranean against Metaponto would have created increased tension within a colony already ravaged by disease. This could have caused the perfect storm to create stasis temporarily ending the period of prosperity.
Keywords: Greece--Antiquities.; Excavations (Archaeology)--Greece.